Lingodeer to develop speaking skills in english with students from level 8th at Unidad Educativa Miguel Egas Cabezas in Otavalo - Córdova Díaz, Inti Sairi (2023)
The use of the LingoDeer application to develop speaking skills with the eighth-level students at Miguel Egas Cabezas high school in Otavalo.